The effect of cell surface components on adhesion ability of Lactobacillus rhamnosus - Polak-Berecka, Magdalena (Springer International Publishing, 2014)
The aim of this study was to analyze the cell envelope components and surface properties of two phenotypes of Lactobacillus rhamnosus isolated from the human gastrointestinal tract. The ability of the bacteria to adhere to human intestinal cells and to aggregate with other bacteria was determined. L. rhamnosus strains E/N and PEN differed with regard to the presence of exopolysaccharides (EPS) and specific surface proteins. Transmission electron microscopy showed differences in the structure of the outer cell surface of the strains tested. Bacterial surface properties were analyzed by Fourier transform infrared spectroscopy, fatty acid methyl esters and hydrophobicity assays. Aggregation capacity and adhesion of the tested strains to the human colon adenocarcinoma cell line HT29 was determined. The results indicated a high adhesion and aggregation ability of L. rhamnosus PEN, which possessed specific surface proteins, had a unique fatty acid content, and did not synthesize EPS. Adherence of L. rhamnosus was dependent on specific interactions and was promoted by surface proteins (42–114 kDa) and specific fatty acids. Polysaccharides likely hindered bacterial adhesion and aggregation by masking protein receptors. This study provides information on the cell envelope constituents of lactobacilli that influence bacterial aggregation and adhesion to intestinal cells. This knowledge will help to understand better their specific contribution in commensal–host interactions and adaptation to this ecological niche.